A programmable array processor architecture for flexible approximate string matching algorithms - Michailidis, P.D.; Margaritis, K.G. (2005 International Conference on Parallel Processing Workshops (ICPPW'05), 2005)
This paper proposes a generic programmable array processor architecture for a wide variety of approximate string matching algorithms. Further, we describe the architecture of the array and the architecture of the cell in detail in order to efficiently implement for both the preprocessing and searching phases of most string matching algorithms. Further, the architecture performs approximate string matching for complex patterns that contain don't care, complement and classes symbols. Our architecture maximizes the strength of VLSI in terms of intensive and pipelined computing and yet circumvents the limitation on communication. It may be adopted as a basic structure for a universal flexible string matcher engine.